Fulvestrant May Falsely Increase 17β-Estradiol Levels in Immunoassays: A Case Report of a 57-Year-Old Postmenopausal Patient With Recurrent Estrogen Receptor-Positive Breast Cancer - Ding, Jingxian; Cao, Yali; Guo, Yonghong (Frontiers in Oncology, 2022)
The prognosis for female patients with locoregionally recurrent breast cancer has improved with the concurrent local and systemic treatment under multiple disciplinary teams. Radiotherapy is a valuable local treatment measure for unresectable locoregional recurrent breast cancer; however, reirradiation in previously irradiated area is still a matter of debate. Antihormonal therapy achieves an overall survival benefit for most of these patients with estrogen receptor positive (ER+) breast cancer both in the adjuvant and metastatic settings. Fulvestrant is an ER antagonist and selective ER downregulator widely used in antihormonal therapy, especially in recurrent postmenopausal ER+ breast cancers. However, fulvestrant closely resembles 17β-estradiol in its molecular structure which may result in false increases in serum 17β-estradiol levels in commercially available immunoassays leading to incorrect medical decisions. Herein, we report a case of a 57-year-old postmenopausal patient with recurrent ER+ breast cancer treated with concurrent fulvestrant and reirradiation. There was a good clinical response and the combination treatment was well tolerable. During the quarterly follow-up, we monitored a gradual increase of the serum 17β-estradiol level in immunoassays, unexpectedly, because the patient underwent natural menopause 8 years ago. To rule out the suspected fulvestrant cross-reactivity with 17β-estradiol in immunoassay, the patient’s serum 17β-estradiol levels were subsequently tested with the more sensitive and specific liquid chromatography-mass spectrometry (LC-MS) method, which confirmed 17β-estradiol levels at postmenopausal level. Concomitant fulvestrant with reirradiation seems to be a safe and effective therapy for locoregionally recurrent ER+ breast cancer. However, a falsely increased 17β-estradiol may result from cross-reactivity between 17β-estradiol and its molecular analog compounds, for example, fulvestrant. Therefore, it is important for the clinicians with the knowledge of this interaction to prevent unnecessary erroneous interpretation of results, and avoid wrong medical decisions.